Protection of Human Rights in Southeast Asia with Special Reference to the Rohingya in Myanmar: A Critical Study of the Effect of ASEAN’s Policy and Action on ASEAN Intergovernmental Commission on Human Rights (AICHR) - Rachminawati, Rachminawati; Mokhtar, Khairil Azmin (Padjadjaran Journal of International Law, 2019)
AbstractSince its inception over four decades ago ASEAN has been working towards improving the lives of its citizens. Year 2009 has opened another chapter with the inauguration of AICHR pursuant to Article 14 of the ASEAN Charter at the 15th ASEAN Summit. Ever since, AICHR has conducted various activities. In the midst of these ?progress?, the vital question remains unanswered; To what extend AICHR has been successful in protecting human rights of citizens in ASEAN countries? This shall be answered through qualitative legal research. This study serves as an analytical basis to predict the future development of the AICHR as well as human rights protection in South East Asia. Furthermore, it contributes to the reform of both ASEAN and AICHR toward implementation of human rights in the region. This research focuses on human rights issues of the Rohingya in Myanmar whereby ASEAN?s policy and action relating to the issue are examined. The finding shows that the policy and action of ASEAN does not provide much support in protecting the rights of the Rohingya. On the contrary, the policy has hindered the effort of AICHR in protecting human rights. AICHR is considered not independent since it almost completely relies on ASEAN. This article thus suggests ASEAN and its member states to take real and concrete measures to protect human rights. In achieving AICHR and ASEAN?s objectives, ASEAN member states must respect human rights and support AICHR with necessary power and measure.Keywords: AICHR, ASEAN, Human Rights, Myanmar, Rohingya. AbstrakSejak kelahirannya empat dekade yang lalu, ASEAN selalu berupaya meningkatkan taraf hidup rakyatnya. Tahun 2009 membuka lembaran baru ASEAN dengan adanya inaugurasi AICHR berdasarkan Pasal 14 dari Piagam ASEAN pada Konferensi Tingkat Tinggi ASEAN ke-15. Semenjak itu, AICHR telah melaksanakan berbagai kegiatan. Dalam perkembangannya, masih terdapat pertanyaan penting yang belum terjawab; sejauh mana keberhasilan AICHR dalam melindungi hak asasi dari warga negara-negara di ASEAN? Untuk menjawabnya, pertanyaan ini akan dijawab melalui penelitian hukum kualitatif. Penelitian ini berfungsi sebagai dasar analisis untuk memprediksi perkembangan AICHR juga perlindungan HAM di ASEAN. Selain itu, penelitian ini diharapkan dapat memberikan berkontribusi terhadap reformasi ASEAN dan juga AICHR dalam perlindungan HAM di ASEAN. Penelitian ini memfokuskan pada isu HAM kelompok Rohingya di Myanmar dengan menelaah kebijakan dan tindakan ASEAN terhadap isu tersebut. Hasil penelitian menunjukkan bahwa kebijakan dan tindakan ASEAN tidak memberikan cukup dukungan dalam perlindungan HAM terhadap Rohingya, namun sebaliknya, kebijakan-kebijakan yang ada telah menghalangi uapaya AICHR dalam melindungai HAM. Sehingga AICHR tidak benar-benar independen sebab AICHR bergantung nyaris sepenuhnya pada ASEAN. Oleh karenanya, ASEAN dan negara-negara anggotanya sebaiknya melakukan berbagai upaya yang nyata dan konkret untuk melindungi HAM. Agar AICHR bisa merealisasikan maksud dan tujuannya, ASEAN dan negara-negara anggotanya harus menghormati HAM dan mendukung AICHR melalui berbagai upaya dan kekuatan yang diperlukan.Kata Kunci: AICHR, ASEAN, Hak Asasi Manusia, Myanmar, Rohingya.